Konstruksi Preposisi Pada dan Kepada dalam Ragam Bahasa Akademis: Kajian Sintaksis Berbasis Korpus - Salsabila, Faradhiba; Yuliawati, Susi; Darmayanti, Nani (Humanis; Vol 27 No 2 (2023)DO - 10.24843/JH.2023.v27.i02.p02, 2023)
Preposition pada and kepada have syntactic role similarities. This makes the prepositions pada and kepada can be substituted for each other in certain situations. The purpose of this study is to investigate the frequency, the pattern of colligation, and the syntactical roles of prepositions pada and kepada in academic variety languages. The theory used to analyze the data are from Alwi et al. (2003), Chaer (2015), Hoey (2005), Ramlan (1987), Saeed (2016), and Slager (2021). This research applies a mixed method research design. This study found that the frequency of the preposition pada appears 662 times, while the preposition kepada is 118 times. The preposition pada often followed by non-personal nominal phrase, while the preposition kepada often followed by personal nominal phrase. Prepositions pada and kepada have the same syntactic role of the goal and recipient